MODERN ASPECTS OF DIAGNOSTICS, TREATMENT AND PREVENTION OF CONGENITAL TOXOPLASMOSIS - M. S. Savenkova; G. M. Balakireva; Yu. L. Ishutina; M. P. Shalatonin (LLC "Diagnostics and Vaccines", 2017)
Diagnostics of intrauterine infection associated with T. gondii, today is a task with an ambiguous solution for different specialists - gynecologists, obstetricians, neonatologists, infectious disease specialists, resuscitators. This problem is interdisciplinary, and its coordinated decision, diagnosis and treatment of this disease at an early stage will reduce the risk of stillbirths, deaths and severe consequences. The article reflects the current literature data on the clinical features of toxoplasmosis in relation to the genotype of Toxoplasmа, circulating in the world. Particular importance is given to the selection of methods for prenatal and postnatal diagnosis of toxoplasmosis. The data of the latest review (2017) of theAmericanAcademy of Pediatrics on the diagnosis, treatment and prevention of congenital toxoplasmosis are presented. The main clinical manifestations of toxoplasmosis were revealed. Basic preparations for treatment of toxoplasmosis is Trimethoprim + sulfamethoxazole (Biseptol) and spiramycin (Rovamycin).